2018
DOI: 10.1007/s00436-018-5754-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Pfdhfr and Pfdhps mutations among asymptomatic pregnant women in Southeast Nigeria

Abstract: Sulfadoxine-pyrimethamine (SP) is the recommended drug for intermittent preventive treatment of malaria in pregnancy in most of sub-Saharan Africa. Resistance to SP is related to mutations in the dhfr and dhps gene of Plasmodium falciparum. This study determined the prevalence of Pfdhfr and Pfdhps polymorphisms found in asymptomatic pregnant women attending antenatal care in Calabar, Nigeria. From October 2013 to November 2014, asymptomatic pregnant women attending antenatal care clinics were enrolled after ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 274 publications
(390 reference statements)
8
13
1
Order By: Relevance
“…As the most frequent mutation of Pfdhps, our findings illustrate the high prevalence of A437G at 79.0% (229/290), which has also been reported to be nearly at a saturation level in most African countries [27]. Furthermore, a higher proportion of A437G has been detected at 75.6% in Gabon [36], 87.9% in Kenya [37], 97.6% (1416/1451) in Congo [12], and 96.4% (27/28) in Nigeria [28]. Thus, it needs to be kept in mind that a high prevalence of SP-resistant parasites is present in these regions.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As the most frequent mutation of Pfdhps, our findings illustrate the high prevalence of A437G at 79.0% (229/290), which has also been reported to be nearly at a saturation level in most African countries [27]. Furthermore, a higher proportion of A437G has been detected at 75.6% in Gabon [36], 87.9% in Kenya [37], 97.6% (1416/1451) in Congo [12], and 96.4% (27/28) in Nigeria [28]. Thus, it needs to be kept in mind that a high prevalence of SP-resistant parasites is present in these regions.…”
Section: Discussionsupporting
confidence: 72%
“…The current survey demonstrated an extremely high prevalence (> 84%) of three mutations (N51I, C59R, and S108N) in P. falciparum clinical isolates imported from Africa and SEA. In Africa, Pfdhfr nonsynonymous polymorphisms have also been reported at high frequencies in isolates from Uganda [26], Angola [27], the Democratic Republic of the Congo [12], Nigeria [28], and Sierra Leone [29]. Parasitic infections carrying the Pfdhfr triple mutant (IRNI) are significantly more likely to be resistant to SP treatment than infections with fewer Pfdhfr mutations [30].…”
Section: Discussionmentioning
confidence: 99%
“…been shown to have important implications for the effectiveness of SP in children less than 5 years of age and in pregnant women [41]. Reports from previous studies within Nigeria and in Africa were: 37.5% and 22.5% of A437G and K540E haplotype mutations respectively in Lagos (2011) [9] and 96.4% of 437G haplotype and no mutation at K540 codon in Calabar (2013/2014) [42], Table 6 Distribution of dhps mutations at the community locations in Lagos, Nigeria…”
Section: Discussionmentioning
confidence: 99%
“…As The WHO recommends that SP-IPTi has been reported from recent surveys in Africa, we confirmed that virtually no cases imported into China in this temporal interval lacked drug-resistance mutations. For context, mutations N51I, C59R and S108N were reported as universal (or nearly so) in Gabon and southeast Nigeria (Bouyou-Akotet et al, 2015; Esu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%